PENGARUH PENERAPAN TERAPI SEFT (SPRITUAL EMOTION FREEDOM TECHNIQUE) TERHADAP PENURUNAN IMSOMNIA DI PANTI JOMPO BHAKTI ABADI BALIKPAPAN - Euis Yuniastuti (Universitas Tridharma, 2021)
In the elderly, the problem of insomnia tends to have the potential to cause physical and mental health problems in particular. Insomnia is a condition when a person has difficulty sleeping or cannot sleep well and can make the elderly more susceptible to several diseases. This insomnia disorder can be overcome by SEFT therapy. Spiritual Emotional Freedom Technique (SEFT) including relaxation techniques, is a form of mind-body therapy of complementary and alternative therapies in nursing. SEFT is a technique of combining the body's energy system (energy medicine) and spiritual healing using the tapping method at certain points on the body (Zainuddin, 2009). This type of research uses a quasi-experimental design using a two-group pretest-posttest design with control group design Research sample of 30 elderly people (15 people including the experimental group and 5 people including the control group) The results of this study explain that SEFT therapy is effective in reducing insomnia In the elderly at the Bhakti Abadi Nursing Home in Balikpapan, there was a change in the mean value of insomnia where before being given SEFT therapy the average insomnia was 28.93 which was included in the severe category and after being given SEFT therapy had an average value of 23.53 which was included in the mild category Keywords: Insomnia, SEFT Therapy